Manajemen Pembelajaran Bahasa Arab di Lingkungan Anak Usia Dini - Ummidlatus Salamah; Fashi Hatul Lisaniyah; Maulidiyana Lailiyah (Alzam: Journal of Islamic Early Childhood Education, 2024)
This research discusses the management of Arabic language instruction at RA Nurul Jadid Sembungrejo Plumpang, Tuban, aiming to understand the effectiveness of management approaches applied in introducing Arabic to early childhood students. Using a qualitative approach and field study methods, data were collected through in-depth interviews, participatory observation, and documentation, then analyzed using the Miles and Huberman interactive model. The study findings indicate that the learning management process includes planning, organizing, implementation, and evaluation phases, designed to create a structured and enjoyable learning environment. In planning, selected materials are relevant and age-appropriate, while the organization and implementation stages focus on utilizing engaging media and interactive methods to attract children's interest. Evaluation is conducted through direct observation and worksheets to assess students' understanding of Arabic vocabulary. The study concludes that effective learning management at RA Nurul Jadid not only aids students in mastering Arabic basics but also holistically supports their cognitive and spiritual development.